Keldysh tuning of photoluminescence in a lead halide perovskite crystal - Zhuquan Zhang; Honglie Ning; Zi-Jie Liu; Jin Hou; Aditya D. Mohite; Edoardo Baldini; Nuh Gedik; Keith A. Nelson (Proceedings of the National Academy of Sciences, 2025)
In 1964, Keldysh laid the groundwork for strong-field physics in atomic, molecular, and solid-state systems by delineating a ubiquitous transition from multiphoton absorption to classical field-driven electron tunneling under intense electromagnetic waves. While both processes in semiconductors can generate carriers and result in photon emission through electron–hole recombination, the low quantum yields in most materials have hindered direct observation of the Keldysh crossover. Leveraging the large quantum yields of photoluminescence in lead halide perovskites, we show that we can not only induce bright light emission from extreme subbandgap excitation but also distinguish between photon-induced and electric-field-induced processes. Our results span the transition between quantum-mechanical and classical field effects of the light and provide generalizable insights into the nonequilibrium dynamics that result from strong-field light–matter interactions. The findings also open avenues for light upconversion and subbandgap photon detection, highlighting the potential of lead halide perovskites in advanced optoelectronic applications.